Characterising root attachment in Rhizobium-legume symbioses - Parsons, J (2020)
In Rhizobium-legume symbioses the earliest stage of physical contact between bacteria and the plant root is primary root attachment. This is crucial for nitrogen-fixing symbiosis development and underpins many plant growth-promoting relationships. Rhizobia use a variety of factors for primary attachment including pH-dependent adhesins (such as glucomannan and the hypothesised rhicadhesin), surface proteins and extracellular polymeric substances. However, primary attachment remains an understudied area of symbiosis development. In this work I use a range of techniques including luminescence-based attachment assays, mariner insertion sequencing (INSeq) and real-time imaging to investigate the factors governing primary attachment to plant roots with the model organism Rhizobium leguminosarum biovar viciae 3841. These techniques demonstrate that bacterial cell surface and extracellular factors are crucial and show extensive pH-condition and plant host specificity. Exopolysaccharide, lipopolysaccharide and peptidoglycan all show different profiles of modification in attachment to pea roots at different pHs and attachment to barley and soybean roots. The glycolytic enzyme TpiA is likely to be surface localized and is an attachment factor required under all conditions. Further, outer membrane protein and Flp/Tad pilus usage in attachment to soybean and barley roots shows that Rlv3841 can use primary attachment mechanisms demonstrated in other bacterial species. Another novel insight is that a filamentous hemagglutinin adhesin factor is also a previously unknown primary attachment factor. Proteomics, attachment assays, INSeq and confocal imaging were used to investigate rhicadhesin, demonstrating that there are multiple attachment factors matching the criteria for this protein. As glucomannan-independent root hair attachment is shown to be both polar and non-polar, these factors are likely distributed across the cell surface. Results from INSeq showed that control of cyclic-di-GMP levels is another important parameter in root attachment. It seems likely that the regulator RL4145 (required for attachment to all plants tested) functions via repression of a cyclic-di-GMP degrading factor to promote attachment. This work also builds on root-microbe interaction imaging technologies by developing a system suitable for Rhizobium and legume plants. Results reinforced the idea that the root elongation zone is a crucial region for early stage interactions, and that bacterial cell motility is important for this. Overall, this work significantly enhances our understanding of primary attachment mechanisms in Rhizobium-legume symbioses, demonstrating a previously unknown mechanistic complexity.